2019
DOI: 10.1007/978-3-030-30642-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional State Recognition with Micro-expressions and Pulse Rate Variability

Abstract: Machine learning has known a tremendous growth within the last years, and lately, thanks to that, some computer vision algorithms started to access what is difficult or even impossible to perceive by the human eye. It is then natural that scientists began looking for ways to probe humans' emotions and their psyche with this technology. In this paper, we study the feasibility of recognizing and classifying the abstract concept of emotional states from videos of people facing a regular RGB camera. We do so by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results showed that the accuracy of the classification is around 66%-83% for different stress levels. Belaiche et al [17] used both micro-expressions and PRV to predict three emotion states, namely, happiness, disgust and anger. This study found that although the accuracy of the PRV based method is higher than the micro-expressions based method in emotion states recognition but the average accuracy is usually not higher than 60% for the dataset that contains sudden emotion change.…”
Section: Stress and Emotion Detection With Rppg Frameworkmentioning
confidence: 99%
“…The results showed that the accuracy of the classification is around 66%-83% for different stress levels. Belaiche et al [17] used both micro-expressions and PRV to predict three emotion states, namely, happiness, disgust and anger. This study found that although the accuracy of the PRV based method is higher than the micro-expressions based method in emotion states recognition but the average accuracy is usually not higher than 60% for the dataset that contains sudden emotion change.…”
Section: Stress and Emotion Detection With Rppg Frameworkmentioning
confidence: 99%